Legislasi Etik : Sebuah Alternatif Solusi Bagi Legitimasi Baru Legislatif - Denny Hernawan (Centre for Public Policy and Management Studies, 2004)
Public criticism about “budgetary party” conducted by Local Legislative Body (DPRD) in past two years reveals how impartant to set up instruments or tools that would be effectively control the body. Beside political approach, ethical approach to this issue will give another perspectives on how public organization or public officials should operate. Based on this approach, there are 3 conflicting sources that resulted in irresponsible, or unatehical, action of public organizations as follow : conflict of authority, conflict of interest, and conflict of role. In order to eliminate negative impact of those conflicting aspects, we have to consider ethics solution as viable alternatives. One of the important steps is put ethics legislation (or ethics law) on policy agenda. It is essential to adopt the law that would regulate public organizations or public officials comply with their ethical action in area such as financial exposure, campaign financing and so forth. Furthermore, some basic principles of limitation should be considered as compelling frameworks.Assuming that there is a strong political commitment from supra-political structure on legislative reform, the possibility of the law to be implemented is relatively high since sociopolitical setting has changed significantly. The establishment of Ethics Commission (or other names) and Ethics Code in Legislative Act (UU no. 22/2003), the consistency of media to disclose the issues, and the result of legislative general election are some important factors for us to be more optimistic.Kata kunci: legislatif, kepentingan publik, perilaku tidak etis, etika, responsibilitas